ULTRASOUND GUIDED PERCUTANEOUS ASPIRATION OF UDDER ABSCESS IN DAIRY COWS WITH CHRONIC MASTITIS - M. Venkatesan; K. Jayalakshmi; B. Poovarajan; M. Saravanan; S Yogeshpriya; P Selvaraj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A retrospective study was carried out to assess the udder affections of cows that were presented to the Large Animal Medicine Referral Clinic of Veterinary College and Research Institute, Thanjavur, Orathanadu, Tamil Nadu during June 2017 to April 2018. In this study involving 161 cows, 4 cows were found to have udder swelling / abscess diagnosed by ultrasound and percutaneous aspiration done under sonagraphic guidance. Udder ultrasound revealed hyperechoic alveolar tissue with anechoic/ heterogenous content in the affected quarters. Aspirated samples were culturally positive for the isolate Staphylococcus aureus and E. coli. In vitro antibiotic sensitivity test showed highest susceptibility to streptomycin followed by enrofloxacin and ciprofloxacin, gentamicin and amoxycillin with good recovery on treatment.